PURWARUPA SISTEM PERINGATAN DINI BANJIR BERBASIS ARDUINO UNO - Hariyadi Hariyadi; Hendro Nurkholis Ulfa (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Currently there is no flood warning system that able to work real-time and automaticly to determine the height of the water level of the river. It could cause the citizen around the area do not get the information about the river overflow as soon as possible. This project designed a flood warning system that works automatically by monitoring the height (level) of water in the river. This warning system using an ultrasonic sensor-based microcontroller, which will determine the water surface elevation based on certain levels. When the water level reaching the the top post, it will give a quick information of the danger.